The European Union as a Global Counter-Terrorism Actor (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. After the death of Osama Bin Laden and the demise of Al Qaeda, the EU is increasingly threatened by new jihadi terrorist groups such as ISIS, as exemplified by recent terror attacks on Paris, Brussels, Nice, Berlin and Manchester. This book investigates the role of the EU in dealing with such groups as part of its counter-terrorism efforts, by outlining the increasing role of the EU as an external counter-terrorism actor.